Managing interests, a methodology for determining the degree of influence within a project and managing its risk: The case of the Pasacaballos fishermen and the expansion of the Oiltanking Cartagena wharf (LACCEI, 2024)
Within project management it is important to distinguish, recognize and manage the relevant stakeholders of the project, due to this, the objective of this article is to analyze the different influence strategies that can be used by stakeholders and how to manage them in the different phases of the life cycle of a project. In this article, the population under study is the Pasacaballos community and its impact on the development of the Oiltanking Cartagena loading dock expansion project, in the year 2022, the case-study focuses on three aspects: power analysis, legitimacy and urgency for the analysis of the intentions of secondary stakeholders. The main findings are that based on the fundamental type of influence strategy used by stakeholders and recognizing the stage of the project life cycle, an effective management model can be developed to dilute the influence of stakeholders or minimize the impact that their actions may have on the development of the project's decision-making proces